2021
DOI: 10.1097/md.0000000000026560
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of left bundle branch pacing in comparison with conventional right ventricular pacing

Abstract: Background: Right ventricular pacing (RVP) has been widely accepted as a traditional pacing strategy, but long-term RVP has detrimental impact on ventricular synchrony. However, left bundle branch pacing (LBBP) that evolved from His-bundle pacing could maintain ventricular synchrony and overcome its clinical deficiencies such as difficulty of lead implantation, His bundle damage, and high and unstable thresholds. This analysis aimed to appraise the clinical safety and efficacy of LBBP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Indeed, recent studies have demonstrated that LBPaP produces better LV mechanical synchrony than RVSP, 14 , 23 , 28 which is consistent with the results of our recently published meta-analysis. 29 In our study, IVMD and SPWMD were lower in the LBBaP group in comparison with the RVSP group, further suggesting that LBBaP could generate better ventricular mechanical synchrony than RVSP. Therefore, as a novel physiological pacing mode, LBBaP can produce good ventricular electrical-mechanical synchronization that is similar to the result of the preoperative native conduction system and better than that of RVSP.…”
Section: Discussionsupporting
confidence: 48%
“…Indeed, recent studies have demonstrated that LBPaP produces better LV mechanical synchrony than RVSP, 14 , 23 , 28 which is consistent with the results of our recently published meta-analysis. 29 In our study, IVMD and SPWMD were lower in the LBBaP group in comparison with the RVSP group, further suggesting that LBBaP could generate better ventricular mechanical synchrony than RVSP. Therefore, as a novel physiological pacing mode, LBBaP can produce good ventricular electrical-mechanical synchronization that is similar to the result of the preoperative native conduction system and better than that of RVSP.…”
Section: Discussionsupporting
confidence: 48%
“…Two-dimensional speckle-tracking echocardiography (2D STE) enables quantitative analysis of the degree of deformation in myocardial segments, as well as the scale of contraction dyssynchrony. Previous studies have shown that global longitudinal strain (GLS) and peak systolic dispersion (PSD) enable a more objective, accurate and reproducible assessment of myocardial dysfunction compared with tissue doppler imaging (TDI) or measurement of LVEF [ 8 ], which, so far, have been mainly used to assess the hemodynamic effects of HBP [ 9 , 10 ]. Left atrial volume is a recognised indicator of LV diastolic dysfunction, and it is a good predictor of atrial fibrillation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are two possible reasons for the result: 1) The sample size was small and the duration of follow-up was short; 2) LBBP is able to improve LVEF of HF patients with BBB, while LBBP and RVP have little effect on LVEF in patients with normal cardiac function and shorter QRSd during short-term follow-up. 24 Therefore, more studies with long-term follow-up are needed to confirm our findings in these patients. After placement of an RV lead through the tricuspid valve apparatus, lead-induced TR may be caused by lead-related tricuspid leaflet injury or perforation or lead entanglement, impingement, or adherence to the tricuspid valve.…”
mentioning
confidence: 62%